Organizational Challenges of Development and Implementation of Virtual Reality Solution for Industrial Operation - Saghafian, Mina; Laumann, Karin; Skogstad, Martin Rasmussen (Frontiers in Psychology, 2021)
This research investigated the organizational challenges related to the development and implementation of virtual reality technology for operation in a conservative heavy machinery industry. The incorporation of a virtual reality solution for heavy machinery equipment enhanced the safety and convenience of operation under dangerous work conditions. However, the development and implementation processes faced challenges. Furthermore, the adoption of the solution by users was perceived to be slower than anticipated. We aimed to explore the main challenges that the developer organization faced and how it also influenced user organizations. Due to the exploratory nature of the research, qualitative analysis was chosen, interviews were conducted, and thematic analysis was applied. The themes and subthemes were identified and discussed. The results showed the existence of challenges related to technology maturity, managerial challenges regarding communication and support coordination, workload, and multiple stakeholder management. The findings emphasize the importance of attending to the existing and potential organizational challenges before and throughout technological innovation. Theoretical and managerial implications are discussed, and a future research agenda is suggested